1993
DOI: 10.1111/j.1471-4159.1993.tb05842.x
|View full text |Cite
|
Sign up to set email alerts
|

A Brain‐Specific Protein p25 Is Localized and Associated with Oligodendrocytes, Neuropil, and Fiber‐Like Structures of the CA3 Hippocampal Region in the Rat Brain

Abstract: Developmental expression and cellular localization of a novel brain-specific 25-kDa protein (p25), a substrate of tau protein kinase II, were investigated in the rat brain using polyclonal antibodies raised against peptides synthesized based on the p25 amino acid sequence. By western immunoblotting, p25 was found to be expressed only slightly in the embryonic period; the expression increased from 11 days up to 5 weeks of age, and continued to increase gradually until 1-2 years of age. Immunohistochemistry reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 21 publications
6
72
1
1
Order By: Relevance
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 82%
“…9). The specificity is further supported by the unique fact that the assembly of these two disordered hallmarks occurs exclusively at pathological conditions since in normal brain SYN and TPPP/p25 are expressed in neurons [57,58] and oligodendrocytes [9,59], respectively. Previously we showed that TPPP/p25, similarly to SYN, could be taken up by cells from the medium [35].…”
Section: Discussionmentioning
confidence: 82%
“…It is known that both TPPP1 and TPPP3 can be found in adult brains of various mammals. The exact localization of TPPP3 in brain is not known but TPPP1 can be found physiologically in oligodendroglia not in neurons [21][22][23]. Whilst TPPP1 seems to be brain-specific, TPPP3 has been found in other tissues as well [24][25][26].…”
Section: Tppps Of the Zebrafish (Danio Rerio)mentioning
confidence: 99%
“…The developmental expression of TPPP1 in rat brain shows that it is practically absent in embryos and after birth its amount increases continuously by aging [21]. On the contrary, mammalian TPPP2 is absent in adult brain but is expressed in fetal one [27]; i.e.…”
Section: Tppps Of the Zebrafish (Danio Rerio)mentioning
confidence: 99%
“…However, the protein has been found only in rats and bovines (8). Immunohistochemical studies showed TPPP/p25 in oligodendrocytes of human brain tissue and to be increased by age (22). By a novel affinity technique, TPPP/p25 was found in association with rat complexin, one of the ten structural proteins probably involved in synaptic structural reorganization (23).…”
mentioning
confidence: 99%